Pengaruh Pemberian Anestesi Induksi Sevofluran Dengan Penurunan Hemodinamik Pada Pasien General Anestesi di RSUD Labuha Halmahera Selatan - Permata Sari, Ayu Eka; Suandika, Made; Firdaus, Eza Kemal (Madani: Jurnal Ilmiah Multidisiplin, 2024)
General anesthesia involves a complete loss of consciousness. General anesthesia can be given to patients by intravenous injection or by inhalation (Royal College of Physicians (UK), 2011). Inhalation anesthesia is a drug in the form of a volatile gas or liquid, which is administered through the patient's respiratory system (Edgington et al., 2018). Hemodynamics is the flow of blood in the body's circulatory system, either through the magna circulation (large circulation) or the parva circulation (circulation in the lungs). Under normal conditions, hemodynamics will always be maintained in physiological conditions with neurohormonal control (Muftilov et al., 2021). The study aims to determine the effect of administering sevoflurane inhalation induction anesthesia on decreased hemodynamics. This research method is quantitative descriptive with data collection techniques using the observation method. The results of the analysis using the Wilcoxon test with SPSS 22. The results of the study using 44 respondents were used as research samples to determine the effect of administering sevoflurane inhalation induction anesthesia on decreased hemodynamics. From the results obtained that blood pressure 000, pulse.0-013, respiration 0 .001 and MAP .000 which concluded there is an influence between the administration of sevoflurane on the decrease in patient hemodynamics before induction and after induction, while for oxygen saturation 1,000 which concluded no significant influence between the administration of sevoflurane on the decrease in hemodynamics.